KEBIJAKAN SINGAPURA MENGHADAPI INDUSTRI TRANSPORTASI ONLINE: STUDI KASUS MASUKNYA GOJEK KE SINGAPURA - Yolanda Sari Silitonga; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study focuses on Singapore's policy in facing the online transportation industry. Technological developments have encouraged the emergence of various new businesses with high technology utilization, such as e-commerce, fintech, online ticket-booking, and ride-hailing. Indeed, countries in the world still have to continue to study and see feedback from the public and business actors on the policies that have been issued to regulate the implementation of this new business, so that they can formulate the most appropriate policies and create conducive market conditions. Gojek responded to the merger of Grab and Uber as an opportunity to expand the market in Singapore. The Singapore government sees this merger has caused a significant reduction in competition.This research uses library research method. This method describes the phenomena that occur in order to obtain objective and accurate conclusions. This study uses a neorealism perspective and a nation-state level of analysis. This research uses economic nationalism theory and the concept of competition policy.Overall, the Singapore government issued the Point-to-Point Passenger Act of 2019 as a policy to maintain and ensure that online taxis can operate alongside other public transportation. This regulation contains about realizing an open and innovative market, so that Gojek's entry into Singapore is in line with the contents of the regulation, following the decreased competition due to the merger of Grab and Uber. The entry of ride-hailing service businesses to Singapore has been proven to reduce costs and increase the income of online taxi drivers. The Singapore government wants a healthy and pro-competitive online transportation market.Key words: Economic Nationalism Theory, Neorealism, Point-to-Point Passenger Act of 2019